Step
*
1
2
of Lemma
qabs-qsum-qle
1. n : ℤ
2. 0 < n
3. ∀[E:ℕn - 1 ⟶ ℚ]. ∀[x:ℚ].  |Σ0 ≤ j < n - 1. E[j]| ≤ ((n - 1) * x) supposing ∀j:ℕn - 1. (|E[j]| ≤ x)
4. E : ℕn ⟶ ℚ
5. x : ℚ
6. ∀j:ℕn. (|E[j]| ≤ x)
⊢ |Σ0 ≤ j < n. E[j]| ≤ (n * x)
BY
{ (RWO "sum_unroll_hi_q" 0 THENA Auto) }
1
1. n : ℤ
2. 0 < n
3. ∀[E:ℕn - 1 ⟶ ℚ]. ∀[x:ℚ].  |Σ0 ≤ j < n - 1. E[j]| ≤ ((n - 1) * x) supposing ∀j:ℕn - 1. (|E[j]| ≤ x)
4. E : ℕn ⟶ ℚ
5. x : ℚ
6. ∀j:ℕn. (|E[j]| ≤ x)
⊢ |Σ0 ≤ j < n - 1. E[j] + E[n - 1]| ≤ (n * x)
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  0  <  n
3.  \mforall{}[E:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbQ{}].  \mforall{}[x:\mBbbQ{}].
          |\mSigma{}0  \mleq{}  j  <  n  -  1.  E[j]|  \mleq{}  ((n  -  1)  *  x)  supposing  \mforall{}j:\mBbbN{}n  -  1.  (|E[j]|  \mleq{}  x)
4.  E  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbQ{}
5.  x  :  \mBbbQ{}
6.  \mforall{}j:\mBbbN{}n.  (|E[j]|  \mleq{}  x)
\mvdash{}  |\mSigma{}0  \mleq{}  j  <  n.  E[j]|  \mleq{}  (n  *  x)
By
Latex:
(RWO  "sum\_unroll\_hi\_q"  0  THENA  Auto)
Home
Index